The preservation of somatic embryos of papaya derived from papaya lateral shoots after being stored in cryopreservation to maintain plant genetic information in the future - DINI HERVANI; DARDA EFENDI; M. RAHMAD SUHARTANTO; BAMBANG S. PURWOKO (Society for Indonesian Biodiversity, 2018)
Hervani D, Efendi D, Suhartanto MR, Purwoko BS. 2018. The preservation of somatic embryos of papaya derived from papaya lateral shoots after being stored in cryopreservation to maintain plant genetic information in the future. Biodiversitas 19: 724-729. Germplasm storage of papaya is very important because this plant easily adapts to genetic changes due to environmental conditions and open system pollination, so it is necessary to retain the current genetics resources in order to conserve the genetic information. The storage of the vegetative part of the plant with cryopreservation is expected to retain the plant's genetic information in the future. Cryopreservation is the method for germplasm storage using liquid nitrogen at temperature of -196oC This experiment aimed to obtain the growth ability of papaya lateral shoots to produce somatic embryos after being stored by cryopreservation. The experiment was designed in factorial by Completely Randomized Design with two factors.The first factor was the immersion time duration in PVS2 as cryoprotectant solution with 5 treatments of immersion duration of 0, 10, 20, 30, and 40 minutes. Second factor was culture medium for cultivated the lateral shoot which was added with plant growth regulators such as BA (benzyl adenine) and NAA (naphthalene acetic acid) at levels of 0, 1, 2, 3, and 4 mg l-1, respectively. The results showed that the immersion of lateral shoot in cryoprotectants for 10 and 20 minutes gave the better plantlet survival rate after discharge from liquid nitrogen, while the treatment of culture media had not been significant difference.